Running on fear: immigration, race and crime framings in contemporary GOP presidential debate discourse - Brown, Jessica Autumn (Critical criminology, 2016)
This analysis explores the use of "race-baiting," known herein as "racially divisive appeals" (RDAs), and crime frames in Republican (GOP) presidential debate discourse during the 2008 and subsequent election cycles. RDAs which mobilize images of minorities as criminals, terrorists, or as populations engaged in voter or welfare fraud, are analyzed. While the strategic exploitation of racial animus in American politics has tended to be associated with the "Southern Strategy," wherein GOP politicians wooed southern whites by fueling anxieties about blacks, this research finds that modern RDAs focus more on appealing to fears about immigrants. Reasons for this shift, as well some of the varied discursive techniques and narrative content of contemporary RDAs, are explored.